Thickness Dependent on Photocatalytic Activity of Hematite Thin Films. (11th December 2011) - Chen, Yen-Hua; Tu, Kuo-Jui
Abstract : Hematite (Fe2 O3 ) thin films with different thicknesses are fabricated by the rf magnetron sputtering deposition. The effects of film thicknesses on the photocatalytic activity of hematite films have been investigated. Hematite films possess a polycrystalline hexagonal structure, and the band gap decreases with an increase of film thickness. Moreover, all hematite films exhibit good photocatalytic ability under visible-light irradiation; the photocatalytic activity of hematite films increases with the increasing film thickness. This is because the hematite film with a thicker thickness has a rougher surface, providing more reaction sites for photocatalysis. Another reason is a lower band gap of a hematite film would generate more electron-hole pairs under visible-light illumination to enhance photocatalytic efficiency. Experimental data are well fitted with Langmuir-Hinshelwood kinetic model. The photocatalytic rate constant of hematite films ranges from 0.052 to 0.068 min -1 . This suggests that the hematite film is a superior photocatalyst under visible-light irradiation.